2021
DOI: 10.1002/trc2.12231
|View full text |Cite
|
Sign up to set email alerts
|

Novelty‐like activation of locus coeruleus protects against deleterious human pretangle tau effects while stress‐inducing activation worsens its effects

Abstract: The earliest abnormality associated with Alzheimer's disease (AD) is the presence of persistently phosphorylated pretangle tau in locus coeruleus (LC) neurons. LC neuron numbers and fiber density are positive predictors of cognition prior to death. Using an animal model of LC pretangle tau, we ask if LC activity patterns influence the sequelae of pretangle tau. We seeded LC neurons with a pretangle human tau gene. We provided daily novelty‐ or stress‐associated optogenetic activation patterns to LC neurons for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 67 publications
1
34
1
Order By: Relevance
“…This animal model provides the first evidence that LC pretangle tau pathology associated with PC adrenergic dysregulation may drive olfactory dysfunction in preclinical AD stages. The causal effects of PC adrenergic support in olfactory dysfunction observed in this model is further demonstrated by a more recent study (Omoluabi et al, 2021). Combining the pre-tangle tau model with optogenetic stimulation, we demonstrated that a 6 week chronic, learningand positive valence-promoting LC phasic patterned activation (Ghosh et al, 2021), prevented LC fiber degeneration in the PC, and restored olfactory discrimination learning.…”
Section: Norepinephrine and Olfactory Dysfunction In Humans And Anima...supporting
confidence: 76%
See 2 more Smart Citations
“…This animal model provides the first evidence that LC pretangle tau pathology associated with PC adrenergic dysregulation may drive olfactory dysfunction in preclinical AD stages. The causal effects of PC adrenergic support in olfactory dysfunction observed in this model is further demonstrated by a more recent study (Omoluabi et al, 2021). Combining the pre-tangle tau model with optogenetic stimulation, we demonstrated that a 6 week chronic, learningand positive valence-promoting LC phasic patterned activation (Ghosh et al, 2021), prevented LC fiber degeneration in the PC, and restored olfactory discrimination learning.…”
Section: Norepinephrine and Olfactory Dysfunction In Humans And Anima...supporting
confidence: 76%
“…LC pretangle tau, in the absence of amyloid plaques and neurofibrillary tangles, leads to degeneration of LC input to the PC, correlating with impaired olfactory discrimination learning (Ghosh et al, 2019). The degree of LC fiber degeneration within this model is inversely correlated with olfactory learning performance and preventing this degeneration in the PC rescued olfactory learning deficiency (Omoluabi et al, 2021). Together, LC degeneration is both sufficient and necessary for the olfactory discrimination deficiency observed in this rat model, consistent with a critical role of LC-NE input in the PC in various olfactory functions and learning (Doucette et al, 2007;Mandairon et al, 2008;Shakhawat et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ten hertz phasic (300 ms every 2 s; light pulse duration 30 ms) or 25 Hz tonic stimulation patterns were delivered using Doric software ( Ghosh et al, 2021 ). We have previously shown that light stimulation (10–30 Hz) generated ∼8–15 Hz output in LC neurons in anesthetized rats ( Ghosh et al, 2021 ; Omoluabi et al, 2021 ), which are in the range of LC physiological activation [see discussion in Ghosh et al (2021) ].…”
Section: Methodsmentioning
confidence: 99%
“…With widespread projections throughout the brain, the LC-NE system is well-structured to exert global effects through the ubiquitous release of NE ( Aston-Jones and Cohen, 2005 ). A key component of the stress response, the LC signals arousal and is implicated in cognitive processes such as learning and memory, the flipside of which is its involvement in disorders of learning and memory, such as Alzheimer’s disease ( Berridge and Waterhouse, 2003 ; Sara, 2009 ; Braak et al, 2011 ; Mather et al, 2016 ; Mather and Harley, 2016 ; Omoluabi et al, 2021 ). The LC exhibits two fundamental modes of activity, phasic and tonic, which adjust levels of NE at projection sites ( Aston-Jones and Cohen, 2005 ).…”
Section: Introductionmentioning
confidence: 99%